Investigation of dualband fan-shaped microstrip bandpass filter - Seevan F. Abdulkareem; Zainab Faydh; Dhamyaa H. Al-Nuaimi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
In this study, design and simulation of microtrip bandpass filter is presented using RT/Duroid 6010.2 lm substrate. This filter has fan-shaped topology with small dimensions of 12x12 mm2, designed for dual band frequencies at 3.41 and 6.14 GHz. The insertion loss and return loss of initial band at 3.41 GHz are -0.7 and -38.224 dB respectively and its bandwidth ranged from 3.3561 to 3.48 GHz. On the other hand, for 2nd band at 6.14 GHz, the insertion loss and return loss have been -1.377 and -14 dB respectively with bandwidth ranged from 6.0951 to 6.1782 GHz.